Potential value of red blood cell distribution width in predicting in-hospital mortality in intensive care US population with acute pancreatitis: a propensity score matching analysis - Shaoya He; Yu Shao; Tianyang Hu; Yanan Liu (Scientific Reports, 2023)
Abstract The association between red blood cell distribution width (RDW) and in-hospital mortality in intensive care patients with acute pancreatitis (AP) is inconclusive. We extracted the baseline data, Bedside Index for Severity in Acute Pancreatitis (BISAP) score, Sequential Organ Failure Assessment (SOFA) score, and in-hospital prognosis of intensive care patients with AP from the Medical Information Mart for Intensive Care IV database. Performing binary logistic regression analysis to determine whether RDW is an independent risk factor for in-hospital mortality. By drawing receiver operating characteristic (ROC) curves and comparing the areas under the ROC curves (AUC) to determine the predictive value of RDW for in-hospital mortality, and by conducting survival analysis to evaluate the impact of RDW on survival time in hospital. Before and after the propensity score matching (PSM) analysis, RDW was always a risk factor for in-hospital mortality in patients with AP. The AUC of RDW was comparable to BISAP, while the AUCs of combining RDW and BISAP or SOFA were greater than that of BISAP or SOFA alone. The median survival time of the high-RDW group (RDW > 15.37%, before PSM; RDW > 15.35%, after PSM) was shorter than that of the low-RDW group. Compared with the low-RDW group, the hazard ratios of the high-RDW group were 3.0708 (before PSM) and 1.4197 (after PSM). RDW is an independent risk factor for in-hospital mortality in patients with AP. The predictive value of RDW for in-hospital mortality of patients with AP is comparable to BISAP, and the combination of RDW and BISAP or SOFA scoring system can improve the predictive performance to a certain extent.